أثر الاستقرار السياسي في ماليزيا في تنميتها Impact of Political Stability on Malaysia’s Development - (Abdulhamid), عبد الحميد محمد علي زرؤم (Journal of Islam in Asia (E-ISSN 2289-8077), 2014)
اعتنت هذه الدِّراسة بقضيّة الاستقرار السياسي في ماليزيا، والآثار التنموية التي كان لها كبير الأثر في ما يتمتع به هذا البلد متعدد الأعراق والديانات والثقافات واللغات من رخاء اقتصادي، وانسجام اجتماعي، وتقدم علمي. وقد سعت هذه الدِّراسة إلى تبيان العوامل التاريخية والحضارية التي أسهمت بشكل كبير في استقرار ماليزيا سياسيا، ومن ثم في تنميتها التي نشاهد آثارها اليوم في كل المجالات، حيث أضحت ماليزيا وجهة يقبل عليها السياح، ومركزا تعليميا يؤمه الطلاب، وموطنا ثانيا لكثير من رجال الأعمال والمستثمرين الأجانب. كل ذلك بفضل الاستقرار السياسي الذي تنعم به ماليزيا. ومن أهم ما توصلت إليه هذه الدراسة من نتائج: وجود ارتباط مباشر بين الاستقرار السياسي، والازدهار الاقتصادي، والإبداع الدراسي، والتنمية المستدامة. أن الدول المتخلفة اقتصاديا، المضطربة سياسيا لا توفر الأجواء التي تتيح للدّارسين أن يتفوقوا ويبدعوا، ولرجال الأعمال أن يستثمروا. ***************************************************** This study is aimed at studying the issue of political stability and its effects on development in Malaysia that has a significant impact on economic prosperity, social harmony, and scientific progress enjoyed by the country’s multiethnic, multireligious, multicultural, and multilingual population. This study seeks to identify historical and cultural factors that contributed significantly to the political stability of Malaysia, leading to its development which is observable in all domains as Malaysia has become an attractive tourist destination, education hub attracting many foreign students, and a second home for many foreign businessmen and investors. All of this has become possible because of political stability enjoyed by Malaysia. The most important findings and results of this study include: the existence of a direct connection between political stability and economic prosperity, academic creativity, and sustainable development. Economically underdeveloped and politically disturbed countries do not provide suitable atmosphere for students to excel and to be creative and businessmen to make investments.